2019
DOI: 10.1111/ctr.13581
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods of providing analgesia after pancreas transplant: IV opioid analgesia versus transversus abdominis plane block with liposomal bupivacaine or continuous catheter infusion

Abstract: Background: Current practices emphasize a multimodal approach to perioperative analgesia due to higher efficacy and decreased opioid usage. Analgesia for pancreas transplant (PT) has traditionally been managed with intravenous (IV) opioids, and reports of transversus abdominis plane (TAP) blocks are limited in this population.Methods: Three interventions were compared in adult PT patients, including IV opioids, TAP catheter, and TAP block with liposomal bupivacaine. Time to return of intestinal function and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…This may be owing to the high-volume nature of the PVB block; therefore, continuous infusion of 10 mL/h might be less effective in providing analgesia. 24 Given these results, and the faster placement time for single-injection PVB, the authors would favor using the single-injection PVB for any patients who are not ideal candidates to receive TEA. Future studies might examine the use of liposomal bupivacaine in the PVB to determine if longer duration analgesia can be provided.…”
Section: Discussionmentioning
confidence: 99%
“…This may be owing to the high-volume nature of the PVB block; therefore, continuous infusion of 10 mL/h might be less effective in providing analgesia. 24 Given these results, and the faster placement time for single-injection PVB, the authors would favor using the single-injection PVB for any patients who are not ideal candidates to receive TEA. Future studies might examine the use of liposomal bupivacaine in the PVB to determine if longer duration analgesia can be provided.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that TAP catheters are not superior to single‐injection TAP blocks are likely relevant to other abdominal surgeries. A recent study showed that a single TAP block of liposomal bupivacaine produced lower pain scores after pancreas transplant compared with ropivacaine by TAP catheters 16 . Transversus abdominis plane catheters were also shown to be less effective than thoracic epidural analgesia for incisional hernia repair 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Yeap et al conducted a retrospective, single-center study of 197 pancreatic transplants performed from 2009 to 2017 and compared 3 interventions: intravenous (IV) opioids (N ¼ 62, 32%), transversus abdominus plane (TAP) catheter with continuous 0.2% ropivacaine (N ¼ 89, 45%), and single-shot TAP block with liposomal bupivacaine (N ¼ 46, 23%). 1 Immediate postoperative pain scores were lowest for the IV opioid group (P < .001); however, opioid use during postoperative days (PODs) 1 to 5 was lower for both TAP block groups (mean [SE] required daily morphine equivalents in mg were 113 [18.6], 90 [7.5], and 63 [6.8] for standard care, TAP catheter, and liposomal bupivacaine groups, respectively, P ¼ .03). Time to bowel function was faster for the TAP block groups (P < .05) than for the IV opioid group, with times to first oral intake of 12 and 14 hours versus 26 hours (P < .001).…”
Section: Pancreas Transplantationmentioning
confidence: 99%
“…This evidence supports integration of TAP blocks into a multimodal analgesic plan for postoperative pain control after pancreatic transplantation and may allow for decreased opioid use and faster intestinal recovery. 1…”
Section: Pancreas Transplantationmentioning
confidence: 99%